Actividad biológica de lectinas obtenidas de Amaranto (Amaranthus Caudatus) y Chocho (Lupinus Mutabilis). Riobamba, 2020. - Lara Vizuete, Jhonathan Ulises (2020)
This project was carried out in the laboratories of the National University of Chimborazo, Edison Riera campus. The lectins isolated from aqueous extracts of native Andean grains Amaranth (Amaranthus caudatus) and Chocho (Lupinus mutabilis) acquired in the markets of Riobamba, from each species of grain, aqueous extracts obtained by mechanical disruption with mortar adding physiological saline solution, the crushing filtered with a thin nylon mesh, subsequently it centrifuged to obtain a clear supernatant. The biological activity of the lectins determined by evaluating in the aqueous extracts, the hemagglutinating action on a suspension of human red blood cells at 5% of blood groups A, B and O, the procoagulant or anticoagulant action on human plasma with the help of the measurement of TP and aPTT coagulation times and antibacterial action using the Kirby Bauer technique on three bacterial strains Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 29212 and Staphylococcus aureus ATCC 25923. The results of the laboratory tests with respect to hemagglutination showed that both extracts had a very strong agglutination for the three mentioned blood groups, likewise anticoagulant activity demonstrated in the extract of Chocho since it managed to significantly prolong both clotting times. On the other hand, the Amaranth extract showed procoagulant activity by shortening the aPTT, finally, no antibacterial action evidenced by both extracts on the bacterial strains used for the study in comparison with the control antibiotics.